The graph Y=(x^3)-4(X^2)+X+6 is stretched horizontally by a factor of 2 about the line X=4.

What is the resulting equation?

Expert Answers

An illustration of the letter 'A' in a speech bubbles

To stretch a graph horizontally across x=0, you replace every instance of "x" with "x/2" (so basically x has to be twice as large to get the same y value)

We don't want our stretch at x=0, we want it at x=4

To do that, we first move our graph 4 units to the left, then do the stretch, then move it back. To translate our graph, we replace every "x" with "x+4" (so basically, x has to be 4 less than it used to to get the same y value)

Our original graph:

`y=(x^3)-4(x^2)+x+6`, `x=4`

`y= (x+4)^3-4(x+4)^2+(x+4)+6` , `x=0`

Expanding out our new equation, we get:

`y=(x^3+3x^2(4)+3x(16)+64)-4(x^2+2x(4)+16)+(x+4)+6`

`y=x^3+12x^2+48x+64-4x^2-32x-64+x+4+6`

`y=x^3+8x^2+17x+10`

Now we stretch horizontally by a factor of 2, so we replace the "x"s in the equation with "x/2" :

`y=(x/2)^3+8(x/2)^2+17(x/2)+10`, `x=0`

(Note: the above graph has the same scale as the previous ones, so you can see the stretch without scaling distortion, but is centered differently)

The equation simplifies to:

`y=(1)/(8)x^3+2x^2+(17)/(2)x+10`

Now finally we need to move the graph back, 4 units to the right.  To do that we replace every instance of "x" with "x-4":

`y=(1)/(8)(x-4)^3+2(x-4)^2+(17)/(2)(x-4)+10`, `x=4`

Our final equation simplifies to:

`y=(1)/(8)x^3+(1)/(2)x^2-(3)/(2)x`

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial